In vitro evaluation of stability and hemostatic efficacy of single-donor lyophilized canine plasma - Cha, Sumin; Shin, Chaewon; Kang, Changkeun; Jung, Dong-In; Cho, Kyu-Woan; Bae, Hyeona; Yu, Dohyeon (Frontiers in Veterinary Science, 2025)
IntroductionInterest in lyophilized plasma products has increased. However, data on their use in dogs are limited. This study aimed to evaluate the in vitro stability and hemostatic efficacy of single-donor lyophilized canine plasma.MethodsTen canine plasma units were lyophilized and stored at −80 °C, 4 °C, room temperature, and 38 °C for 45 days. The plasma compositions before and after lyophilization were compared to assess the impact of the lyophilization. The following parameters were assessed to evaluate storage stability: blood gas analysis, biochemical parameters, coagulation profiles [prothrombin time (PT); activated partial thromboplastin time (aPTT); fibrinogen concentration; the activities of coagulation factors II, V, VIII, IX, X, and XII, as well as those of antithrombin (AT); and protein C], and kaolin-activated thromboelastography. Aerobic bacterial cultures were performed using thioglycollate broth to assess sterility. Lyophilized plasma samples were reconstituted to 50, 60, 80, and 100% of the original plasma volume to assess the effects of different reconstitution volumes on plasma components. Total protein, albumin, osmolality, selected coagulation factors (II and V), fibrinogen, and AT were measured and compared across the reconstituted groups.ResultsLyophilization decreased the partial pressure of carbon dioxide and increased the pH. No other significant immediate changes were observed. Plasma stored at −80 °C and 4 °C maintained stable biochemical and coagulation profiles over 45 days of storage, with only a slight but statistically significant decrease in fibrinogen concentrations on Days 30 and 45 for refrigerated conditions when compared with post-lyophilization values. Significant reductions in the activities of coagulation factors II, V, and VIII were observed at room temperature by Day 45, whereas PT, aPTT, and thromboelastography remained within normal reference ranges relative to the post-lyophilization values. Storage at 38 °C led to marked deterioration in coagulation function, as evidenced by the prolonged PT and aPTT, substantial decline in fibrinogen concentrations, and >50% reduction in the activity of all assessed coagulation factors relative to the post-lyophilization values. The AT activity declined for all storage groups, whereas protein C and thromboelastography profiles remained relatively stable, except at 38 °C. No bacterial growth was observed in any reconstituted plasma samples across all storage temperature and time points. Reconstitution at lower volumes (50 and 60%) increased the concentrations of albumin and activities of coagulation factors and osmolality.ConclusionThe lyophilization process did not significantly affect the concentrations or activities of major plasma proteins, including coagulation factors and anticoagulant proteins. Storage at −80 °C and 4 °C for 45 days preserved the stability of biochemical and hemostatic parameters. However, storage at room temperature resulted in minor reductions in select coagulation factors (such as factors II, V, and VIII). PT, aPTT, and thromboelastography parameters remained within the normal reference ranges, confirming the short-term stability of the product. Changes in the reconstitution volume affected plasma concentration and highlighted the potential of lyophilized plasma as a rapid resuscitative product in veterinary medicine.